Type 1 Diabetes and Increased Risk of Subsequent Asthma. Issue 36 (September 2015) - Hsiao, Yung-Tsung; Cheng, Wen-Chien; Liao, Wei-Chih; Lin, Cheng-Li; Shen, Te-Chun; Chen, Wei-Chun; Chen, Chia-Hung; Kao, Chia-Hung; Xiaolin, Zhu.
<x xml:space="preserve">Abstract</x> Abstract The association between type 1 diabetes mellitus (T1DM) and asthma remains controversial and has led to new interest in these 2 disorders. The purpose of this study was to examine the associations among young people with T1DM and asthma and offer a clinical demonstration of the balance between Th1 and Th2 responses. We conducted a retrospective cohort study by using data from the National Health Insurance (NHI) system of Taiwan. The cohort consisted of 3545 T1DM cases and 14, 180 controls established during the 1998 to 2011 period. Of the 3545 T1DM patients, 55.1% were girls and 26.5% were in the age group <8 years. The overall incidence of asthma was 47% higher in the T1DM cohort than in the control cohort (6.49 vs 4.42 per 1000 person-y), with an adjusted hazard ratio (HR) of 1.34 (95% confidence interval [CI] = 1.11–1.62). Moreover, T1DM patients who visited the emergency room (ER) more than twice for diabetes had a higher adjusted HR of 17.4 (95% CI = 12.9–23.6) of developing asthma. The adjusted HR of asthma was 38.6 (95% CI = 28.5–52.2) in T1DM patients who had been hospitalized more than twice for diabetes. We observed a significantly higher incidence of asthma in young patients with T1DM than in the general population. Among young people of T1DM with more ER visits or frequent hospitalization because of diabetes mellitus were associated with risk of asthma, may indicate that poor glycemic control significantly contributes to asthma risk.